Exploring The Dynamics of Cambodian Civil Servants’ Job Satisfaction: Evidence from The General Department of Taxation - Khoun Khak; Sarom Mok; Sivutha Onn; Somuny Som (Cakrawala Repositori IMWI)
The sustainability of successful state organizations depends on the job satisfaction of civil servants; however, high employee turnover rates highlight significant challenges within these organizations. To provide a comprehensive understanding of the factors influencing job satisfaction among Cambodian civil servants at the General Department of Taxation, this quantitative study integrates demographic characteristics, equity, and job satisfaction. Drawing on Herzberg’s Two-Factor Theory and Adams’s Equity Theory, the study examines how demographic variables (e.g., gender, tenure, educational attainment, socioeconomic status, geographic location, and salary), intrinsic factors (e.g., nature of work, promotion opportunities, contingent rewards, and communication), and extrinsic factors (e.g., salary, fringe benefits, operating conditions, and relationships with colleagues) interact to shape overall job satisfaction. The study also investigates how civil servants’ job satisfaction is influenced by perceptions of equity. Using the Spector Job Satisfaction Survey (JSS) and statistical techniques including Principal Component Analysis (PCA), multiple regression analysis, and Multivariate Analysis of Covariance (MANCOVA), the findings revealed significant associations between job satisfaction and variables such as gender, geographic location, perceived equity, and school socioeconomic status. Notably, disparities in compensation and resource allocation were identified as the primary sources of dissatisfaction, whereas intrinsic motivators, such as meaningful work and professional recognition, emerged as key drivers of job satisfaction. By integrating Herzberg’s and Adams’s theoretical frameworks with a novel focus on the interaction among job satisfaction, equity, and demographic characteristics in public sector organizations—an area that has received limited scholarly attention—this study contributes meaningful theoretical insights. The findings underscore the importance of equitable compensation systems, targeted professional development, and supportive leadership structures, offering practical implications for policymakers and senior government leaders.